Implementasi Program PRLB dalam Mendorong Transformasi Sistem Pertanian di Kecamatan Paron, Kabupaten Ngawi, Jawa Timur - Nasha Presly Caurelysia; Aliza Dwi Kusuma Marsetyanti; Zaldi Al Faris; Yusuf Hariyoko (Yayasan Lentera Avanya Nagari, 2026)
Ngawi Regency, a national rice granary, introduced the Sustainable Environmentally Friendly Agriculture Program (PRLB) in 2020 to shift from chemical-heavy farming to sustainable organic practices. This qualitative study analyzes the program’s implementation in Paron District using the Van Meter and Van Horn model, focusing on policy standards, resources, interorganizational communication, and agency characteristics. The findings reveal a paradox: while the program offers clear standards—such as using local microorganisms (MOL) and owl-based pest control—and provides adequate structural support (including competent extension workers and effective communication), the farmer adoption rate remains low at only 35–40%. The research demonstrates that structural success is insufficient when implementation requires fundamental behavioral shifts. While resources and agency capacity are strong, adoption is stifled by deep-seated psychosocial factors: conventional habits, a preference for convenience, and resistance to change. Furthermore, the effectiveness of communication channels is heavily mediated by the influence of social opinion leaders. Ultimately, this study concludes that successful policy implementation for behavioral change requires integrating structural-institutional frameworks with behavioral sociology. Policymakers must recognize that farmers act based on practical rationality and socio-cultural contexts, meaning structural inputs alone cannot guarantee the transition to sustainable agricultural practices. Kabupaten Ngawi, sebagai lumbung padi nasional, menghadapi tantangan penurunan produktivitas akibat ketergantungan pupuk kimia. Sebagai solusi, Program Pertanian Ramah Lingkungan Berkelanjutan (PRLB) diluncurkan pada 2020 untuk mentransformasi sistem pertanian menuju praktik organik. Penelitian kualitatif ini menganalisis implementasi PRLB di Kecamatan Paron menggunakan model Van Meter dan Van Horn. Hasil penelitian menunjukkan adanya paradoks implementasi. Secara struktural, program ini memiliki standar kebijakan yang jelas (seperti penggunaan MOL dan burung hantu) serta didukung agen pelaksana yang kompeten dengan komunikasi antarorganisasi yang baik. Namun, tingkat adopsi petani hanya mencapai 35–40%. Analisis mendalam mengungkap bahwa hambatan utama bukan terletak pada sumber daya fisik, melainkan pada faktor psikososial petani. Path dependency (ketergantungan pada pola lama), preferensi terhadap kepraktisan kimiawi, dan resistensi budaya menjadi variabel mediator yang menghambat aksi nyata. Meskipun input struktural memadai, efektivitas program sangat bergantung pada validasi sosial dan peran opinion leaders. Temuan ini memperkaya model Van Meter dan Van Horn dengan menegaskan bahwa kebijakan yang menuntut perubahan perilaku fundamental tidak cukup hanya mengandalkan pendekatan struktural-institusional. Diperlukan integrasi sosiologi perilaku yang memahami kelompok sasaran sebagai aktor dengan rasionalitas praktis dalam konteks sosial-budaya spesifik.